2013
DOI: 10.1007/s10900-013-9694-9
|View full text |Cite
|
Sign up to set email alerts
|

Collective Efficacy and HIV Prevention in South African Townships

Abstract: South African townships have high HIV prevalence and a strong need for collective action to change normative sexual risk behaviors. This study investigated the relationship between perceptions of individuals about collective efficacy in the community’s ability to prevent HIV and their personal HIV risk behaviors. Men (n=1581) and women (n=718) completed anonymous surveys within four Black African Townships in Cape Town, South Africa from June 2008 to December 2010. Measures included demographics, alcohol use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…915 The few studies that have considered the role of collective efficacy on health in sub-Saharan Africa have relied on cross-sectional study designs, have not used validated measures of collective-efficacy, or have measured it at the individual-level. 3133 Our study adds to this body of work by demonstrating that a validated measure of community-level collective efficacy is associated with reduced physical IPV incidence among AGYW in sub-Saharan Africa over time.…”
Section: Discussionmentioning
confidence: 77%
“…915 The few studies that have considered the role of collective efficacy on health in sub-Saharan Africa have relied on cross-sectional study designs, have not used validated measures of collective-efficacy, or have measured it at the individual-level. 3133 Our study adds to this body of work by demonstrating that a validated measure of community-level collective efficacy is associated with reduced physical IPV incidence among AGYW in sub-Saharan Africa over time.…”
Section: Discussionmentioning
confidence: 77%
“…However, social cohesion was weakly positively correlated with neighborhood disadvantage in this study, contrary to theoretical predictions. Cain et al measured perceived collective efficacy among men and women in Cape Town as an individual's belief in their community's capacity to prevent HIV and found this to be associated with reduced frequency and quantity of alcohol use ( Cain et al, 2013 ). It remains to be determined if community collective efficacy shapes alcohol use and HIV acquisition in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Higher neighborhood‐level collective efficacy was associated with lower risk for binge drinking, though results are significant only among the White subgroup. Prior research on collective efficacy and binge drinking are mixed with some studies showing lower binge drinking with a South African sample (Cain et al., ), greater frequency but less drinking per occasion in a New Zealand sample (Lin et al., ), and gender differences, with greater effects for men, in a sample from the Netherlands (Kuipers et al., ). All 3 studies examined individual reports of collective efficacy rather than collective efficacy aggregated to the neighborhood level.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that neighborhood disorder, relative to social cohesion, was a more important factor in alcohol use. Using South African townships, Cain and colleagues () found that those who endorse higher levels of collective efficacy reported less binge drinking. Further research using different neighborhood constructs that also consider potential confounding factors such as social norms is important to clarify the role and importance of collective efficacy in drinking behaviors.…”
Section: Neighborhood Characteristics and Binge Drinkingmentioning
confidence: 99%